Analysis of Factors Affecting The Quality of Regional Development Information on The Teluk Bintuni Regency Government Website - Pandu Agung Dwi Kuncoro; Herningsih Herningsih; Lula Nadia (Publikasi Indonesia, 2026)
This research was conducted to find out why the quality of development information on the Teluk Bintuni Regency local government website is not optimal and what factors affect the lack of quality of development information on the Teluk Bintuni Regency government website. This research method is descriptive research to depict or describe the problem regarding the quality of regional development information on the website of the local government of Teluk Bintuni Regency. The subject of this research is the Department of Transportation, Informatics, and Communication. The results of observations indicate that the quality of regional development information on the website is not optimal, as evidenced by the infrequent updating of development news content and ineffective technical management from data collection to information presentation. The factors contributing to this suboptimal management include inadequate budget allocation, the absence of standard operating procedures (juklak/juknis) as implementation guidelines, poor inter-agency coordination, limited government attention, unsystematic work schedules, insufficient facilities and infrastructure, a shortage of management personnel, low staff competency, and a lack of understanding regarding website management. This study concludes that human resources, competence, and motivation significantly influence the quality of regional development information on the Teluk Bintuni Regency Government website.